Answer:
Step-by-step explanation:

Answer:
<em>D.) 0</em>
Step-by-step explanation:
Its not A. cause 2y−2=0 is y = 1
Its not B. cause 2y−1=0 is y = 1/2
Its not C. cause 2y−3=0 is y = 3/2
Soo... The only option left is D.
It IS D. cause 2y − 0 = 0 is y=0
<em>So you are Correct!!!</em>
<em>hope I helped... <3</em>
<em>Good luck dear :)</em>
First, i put the equation in y=mx+b by dividing 2, since its 2y. since it’s perpendicular we’re talking about you switch the sides (opposite reciprocals). the rest should be self explanatory.
R = sqrt 3 * (V /( pi * h))
V = 62.8
pi = 3.14
h = 15
now we sub
R = sqrt 3 * (62.8 / (3.14 * 15)
R = sqrt 3 * (62.6 / 47.1)
R = sqrt 3 * 1.33
R = sqrt 3.99
R = 1.9 rounds to 2 inches <===
Answer:
f(x) = 3x + 6.
Step-by-step explanation:
f(7) - f(0) = 27 - 6 = 21
so we may write a function:
f(x) = 3x + 6.